(3efGgL GdacQ heHGgL GdYHQs - (3eMeO Hf EHQGgje Hf jMji Hf Ydj GdCfUGQj GdcJHj, LeGd GdOjf, GdeYQha H` GdhWhGW , J (B718 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GQSd LhO LhOg Ydi GdGfGe agei hHYO agPG Gdaf GdKGdK ef Gdafhf GdJi OYJ GdfaS Edi LeYgG s
(3BNQgG (B:s
(3hbO LYd Gddg JYGdi GdTeGA hGdHQcI hGdYOO ai GdVCf hEf cGf dG JdO ai GdSfI EdG eQI s
(3hgh GdKGfi ef Gdbje GdChd fSNI KGfjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B42s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs